Penerapan Pasal 107 Ayat 2 Undang-Undang Nomor 22 Tahun 2009 tentang Keharusan Menyalakan Lampu pada Siang Hari untuk Kendaraan Bermotor di Wilayah Kabupaten Gorontalo - Nasrah Hasmiati Attas; Nursyamsi Ichsan (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
This journal aims to finding out about Application Of Article 107 Verses 2 Of Which Set Lights On Day Of Vechle On The Based Enactment Of The 22 Years 2009 About Traffic And Transportation Street In The Country Of Gorontalo Region. This research aims: 1) to determine what the process application of article 107 verses 2 enactment the day the locomotive in the county of gorontalo. 2) to determine an attemp by the police force in order to prevent and control of article 107 verses 2 enactment the 22 years 2009 in the county of gorontalo. This reseaech is descriptive with an approach empirical juridical. The methods of research used is a method with using basic data and entry with technical technique in collaboration, interviews and literature from a variety of diffrent copies. The population of the research is the whole apparatus of the satres polres gorontalo society. The total number of population was 10 peoples with the used of sampling tecniques. Preventative actions in this manner that the satgas polres gorontalo carrying the arregement. (Making it a number of points in the county gorontalo, traffic lamp) quard and patrol: actions repressive acts thag satted polres gorontalo gave up on an informed on the past by the motors correction in a form of a reform of a body and roll of the research that is on the cross section of polres gorontalo to carry out the sociability of and is the required for the society in both preventive and repressive.